Plant phylogenetic relatedness and herbivore specialization interact to determine pest biocontrol efficiency in mixed plantations - Yang, Qingqing; Chen, Xiaohua (Frontiers in Ecology and Evolution, 2023)
Pest herbivory regulation is one of the key functions provided by diverse ecosystems, especially when compared to species depauperate agro-ecosystems and in the context of increased pest outbreaks due to global change. The dilution effect of host diversity on insect herbivory suggests that mixed plantations are feasible for regulating pest herbivory in agroecosystems. Dilution effect of increased plant diversity on insect herbivory has been widely observed, yet little is known about how it may change with plant phylogenetic relatedness and herbivore specialization, especially at the community level. Here, we compared insect herbivore species richness, abundance and degree of herbivory (i.e., the ratio of trees damaged by pest and total trees in a given area) in monocultures (pure coconut stands and pure pine stands) with generalist and specialist herbivores respectively, with stands mixed with phylogenetically close or distant species in Wenchang city, Hainan Province, China. We found that increasing the number of phylogenetically closely-related tree species could dilute generalist herbivore richness, abundance, and degree of herbivory but amplify specialist herbivore richness, abundance, and degree of herbivory. In contrast, increasing the number of phylogenetically distant tree species increased generalist herbivore richness, abundance, and degree of herbivory, while reducing specialist herbivore richness, abundance, and degree of herbivory. Our results suggest that plant phylogenetic relatedness and herbivore specialization can indeed interact to influence pest control efficiency when using mixed plantations to manage pest herbivory in agroecosystems. Thus, both herbivore specialization and plant phylogenetic relatedness should be taken into account in the management of agro-ecosystems and biodiversity conservation with respect to herbivory.